Impact of Disasters and Emergencies in the Field of Health in Peru - Morales, Nelson (2001)
Disasters are intense disturbances in the environment that produce adverse effects on life and property, exceeding the capacity of community response and requiring external support; adverse events that manage to be served by the community are recognized as emergencies. The extended vulnerability allows certain events reach disastrous proportions.